PENGEMBANGAN PERANGKAT PEMBELAJARAN DENGAN MODEL PBL UNTUK MENINGKATKAN LITERASI MATEMATIS - Budiman, Hendra; Firmansyah, Firmansyah (Universitas Asahan, 2024)
This research aims to 1) To analyze the effectiveness of student worksheets and PISA-based test instruments on the developed PBL model, (2) To analyze the effectiveness of student worksheets and PISA-based test instruments on the developed PBL model. In this research, what will be developed is a PISA-based learning tool and test instrument to improve students' mathematical literacy using the ADDIE (Analysis, Design, Development, Implementation and Evaluation) development model developed by Dick and Carry (1996). The learning tools that will be developed are the Learning Implementation Plan (RPP), Student Worksheets (LKPD) and Evaluation Instruments or Mathematical Literacy Ability Tests. This research was conducted at SMP Negeri 4 Pasir Limau Kapas which is located at Jalan Dua Desa, Teluk Pulai Village, Pasir Limau Kapas District, Rokan Hilir Regency. The results of this research produce products in the form of e-module teaching materials based on problem solving or Problem Based Learning. Based on the results of this research, it can be concluded that the learning tools developed are included in the valid and practical category and the resulting PISA-based learning tools are effectively used in improving students' mathematical literacy skills. This can be seen from the percentage of student learning completeness which exceeds 85%.Keywords: Development, Learning Tools, PISA Based Test Instruments, Problem Based Learning (PBL), Mathematical Literacy